(untitled) (Research, Society and Development, 2021)
Objective: identify the trend of scientific production in Brazilian theses and dissertations about ethical issues and problems among health workers. Methodo: narrative review conducted in the Catalog of Theses and Dissertations of the Coordination for the Improvement of Higher Education Personnel and in the Brazilian Digital Library of Theses and Dissertations. The search took place in July 2020, using the descriptor: “nursing ethics”. 98 studies were recovered, among them 18 productions were included. Thematic analysis of two data was used. Results: of the 18 selected studies, nine were theses and nine dissertations. Two categories were constructed for analysis: Characterization of the studies; Ethical issues involving health problems for workers. Conclusion: the study has identified that the ethical issues involved in work, mostly refer to work overload, lack of material resources, and difficulty in exercising professional’s autonomy, which may be related to the triggering of health problems in workers.